(untitled) (Research, Society and Development, 2020)
Objective: to identify the respiratory diseases prevalent in newborns. Method: analysis of the medical records of newborn patients aged 0 to 28 days, admitted in 2017 to a medium-sized hospital in Serra Catarinense. Methodology: an analysis of the medical records of newborn patients aged 0 to 28 days, admitted in 2017 to a medium-sized hospital in Serra Catarinense. The epidemiological profile, ICD (International Disease Code) of hospitalization and ICD at hospital discharge were analyzed. These data were tabulated in a specific spreadsheet and analyzed using the SPSS statistical software (IBM). Results: they were divided into 2 groups according to the ICDs, according to "ICD J00-J99 diseases of the respiratory system" and "ICD P00-P96 some conditions originating in the perinatal period". From the results it can be seen that the incidence of diseases of the respiratory system (ICD J00-J99) was not influenced by the variables gender, age, type of delivery, weight and gestation period. The respiratory disease that had the highest prevalence was bacterial pneumonia, unspecified with 35%. The results showed that there is a possibility that respiratory diseases are related to diseases originating in the perinatal period (ICD P00-P96). In this period, respiratory distress syndrome (RDS) has the highest prevalence with 37.5%, transient tachypnea of the newborn with 17.5% and meconium aspiration syndrome with 2.5%. The clinical outcome was hospital discharge in most cases. Conclusions: shows the need for preventive measures during prenatal care, in order to avoid prematurity and all associated complications. Favor normal labor and try to avoid elective cesarean sections, also strengthen the practices used in the handling of severe newborns.